D-ɑ-tocopheryl polyethylene glycol succinate: A review of multifarious applications in nanomedicines - Popat S. Kumbhar; Sameer Nadaf; Arehalli S. Manjappa; Niraj Kumar Jha; Sunita S. Shinde; Swapnil S. Chopade; Amol S. Shete; John I. Disouza; Unnam Sambamoorthy; Sanapala A. Kumar (Elsevier, 2022)
Role of excipients in designing diverse dosage forms has been highly acclaimed and needs no introduction. These are integral components of pharmaceutical formulations and determine the structure of a dosage form and its function in drug delivery. In many instances, combating the numerous diseases using active therapeutic agents is ultimately challenging task owing to marred solubility and permeability, multidrug resistance, poor pharmacokinetics and associated toxicities, and stability of the drug itself or delivery system. In that context, excipients modulate product aspects such as stability, biopharmaceutical profile, and patient compatibility. D-ɑ-tocopheryl polyethylene glycol succinate (TPGS) is a FDA approved safe and biocompatible adjuvant and acknowledged in pharmaceutical industries for their notable properties namely solubilizer, absorption and permeation enhancer, emulsifier and stabilizer, etc. Moreover, it performs ample bio-functions like anticancer agent, P-gp and cytochrome P450 inhibitor that eventually assist in escalating the therapeutic performance of the drugs. Furthermore, use of TPGS in nanomedicines is reported to be fruitful in improving anticancer potential and pharmacokinetic properties of relevant molecules. By 2025, the international nanomedicine market is projected to reach USD 350.8 billion. Hence, the TPGS-based nanomedicines can emerge as a promising approach for different diseases and can occupy the market in few years. The present review is focused on the pharmaceutical properties of TPGS with the major emphasis on TPGS-based nanomedicines and drug delivery via different routes. Furthermore, the biological and biomedical properties of TPGS are briefed. Thus, use of TPGS in the development of pharmaceutical formulation can be propitious and thus anticipated to offer better therapeutic performance of the cargo.